Environmental and social factors as predictors of feeding and swallowing disorder in Kingdergarten children in Surakarta - Roy Romey Daulas Mangunsong; Anggi Resina Putri (Poltekkes Kemenkes Bandung, 2026)
Background: Environmental factors such as household cleanliness and the availability of nutritious food, along with social factors such as positive peer interactions and parental support, play an important role in preventing feeding and swallowing disorders among kindergarten children. Objective: This study aimed to analyze the influence of environmental and social factors on the occurrence of feeding and swallowing disorders in children in Surakarta City. Methods: A cross-sectional design was employed from April to August 2025, involving 81 children selected through purposive sampling. The independent variables were environmental and social factors, while the dependent variable was feeding and swallowing disorders. Data were collected through structured interviews, observations, questionnaires, and the Dysphagia Disorder Survey (DDS) instrument. Data analysis was conducted using logistic regression with Stata 13 software. Results: The results showed that children with good environmental factors (OR = 15.15; 95% CI = 0.10–0.38; p = 0.015), positive social factors (OR = 14.57; 95% CI = 0.13 – 0.45; p = 0.016), appropriate age of the child (OR = 13.76; 95% CI = 0.11-0.41; p = 0.019), and high maternal education (OR = 8.43; 95% CI = 0.09 – 0.41; p = 0.042) showed an influence on children's ability to eat and swallow. Conclusion: Environmental and social factors play a significant role in reducing the risk of feeding and swallowing disorders in kindergarten children through family support and a healthy environment.